Unternehmerfamilien Über den Einfluss des Unternehmens auf Lebenslauf, Generationenbeziehungen und soziale Identität - Stamm, Isabell (Verlag Barbara Budrich, 2013)
This empirical study draws a portrait of modern entrepreneurial families - a social unit that has received little attention in scientific discourse so far. The terms life course, biography and everyday life are the guiding concepts of this study. Thus, in contrast to system-theoretical perspectives, the "whole life" of entrepreneurial families is to be taken into account.